9 The mechanics of cardiac contraction and coronary flow: exercise, ischaemia and anti-anginals. (24th April 2016) - Patterson, T; Rivolo, S; Arri, S; Perera, D; Clapp, B; Marber, M; Lee, J; Redwood, S
Abstract : Background: Complex cardiac-coronary interaction has been debated. We developed novel technology (A) and software (B) to analyse real-time simultaneous LV and coronary haemodynamics with delineation of the interdependence during rest, exercise, ischaemia and ISDN in coronary artery disease (CAD). Methods: 25 patients. Coronary measurements (pressure-flow wire) were electronically routed into intracardiac analyser with LV haemodynamics (pressure-volume (PV) loop catheter in LV apex) were measured (rest; exercise ±significant CAD; ISDN) (A). Results: Backward and forward waves in coronary circulation described relative to cardiac mechanics (C). Exercise significantly increased contractility, cardiac work, coronary flow and improved diastolic function (EDPVRB 5.7 ± 0.4;4.8 ± 0.1;p = 0.003) despite increase EDP with leftward, upward PV loop shift (D). Ischaemia was associated with reduction in contractility and mechanical efficiency, driving a rightward and upward shift of PV loop (E). ISDN drove leftward, downward shift of PV loop (F); two-step cardiovascular response 1) significant afterload and cardiac work reduction (1.4 ± 0.4;1.1 ± 0.4J), significant improvement in mechanical efficiency 2) Reduction in preload associated with improved diastolic function (tau38 ± 4;36 ± 4ms;p < 0.01). Conclusion: This is the first demonstration of cardiac-coronary interaction during exercise, ischaemia and ISDN.